Mitophagy: a bridge linking HMGB1 and Parkinson’s disease using adult zebrafish as a model organism - Razali, Khairiah; Mohd Nasir, Mohd Hamzah; Kumar, Jaya; Mohamed, Wael Mohamed Yousef (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
High-mobility group box 1 (HMGB1) has been implicated as a key player in two criticalfactors of Parkinson’s disease (PD): mitochondrial dysfunction and neuroinflammation. However, thespecific role of HMGB1 in PD remains elusive. We investigated the effect of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) administration on mitochondrial dysfunction and HMGB1-associatedinflammatory genes as well as locomotor activity in zebrafish, aiming to elucidate the role of HMGB1in PD. Adult zebrafish received MPTP injections, and locomotor activity was measured at 24- and48-h post-administration. Gene expression levels related to mitophagy (fis1, pink1, and park2) andHMGB1-mediated inflammation (hmgb1, tlr4, and nfkb) were quantified through RT-qPCR analysis.Following MPTP injection, the significant increase in transcript levels of fis1, pink1, and park2 in-dicated notable changes in PINK1/Parkin mitophagy, while the upregulation of hmgb1, tlr4, andnfkb genes pointed to the activation of the HMGB1/TLR4/NFκB inflammatory pathway. Further-more, MPTP-injected zebrafish exhibited decreased locomotor activity, evident through reduceddistance travelled, mean speed, and increased freezing durations. HMGB1 plays a major role incellular processes as it is involved in both the mitophagy process and functions as a pro-inflammatoryprotein. MPTP administration in adult zebrafish activated mitophagy and inflammatory signaling,highlighting the significant role of HMGB1 as a mediator in both processes and further emphasizingits significant contribution to PD pathogenesis